Oil refinery hazardous effluents minimization by membrane filtration: An on-site pilot plant study. (1st October 2016) - Santos, Bruno; Crespo, João G.; Santos, Maria António; Velizarov, Svetlozar
Abstract: Experiments for treating two different types of hazardous oil refinery effluents were performed in order to avoid/minimize their adverse impacts on the environment. First, refinery wastewater was subjected to ultrafiltration using a ceramic membrane, treatment, which did not provide an adequate reduction of the polar oil and grease content below the maximal contaminant level allowed. Therefore the option of reducing the polar oil and grease contamination at its main emission source point in the refinery – the spent caustic originating from the refinery kerosene caustic washing unit – using an alkaline-resistant nanofiltration polymeric membrane treatment was tested. It was found that at a constant operating pressure and temperature, 99.9% of the oil and grease and 97.7% of the COD content were rejected at this emission point. Moreover, no noticeable membrane fouling or permeate flux decrease were registered until a spent caustic volume concentration factor of 3. These results allow for a reuse of the purified permeate in the refinery operations, instead of a fresh caustic solution, which besides the improved safety and environmentally related benefits, can result in significant savings of 1.5 M€ per year at the current prices for the biggest Portuguese oil refinery. The capital investment needed for nanofiltration treatment of the spent caustic is estimated to be less than 10% of that associated with the conventional wet air oxidation treatment of the spent caustic that is greater than 9 M€. The payback period was estimated to be 1.1 years. The operating costs for the two treatment options are similar, but the reuse of the nanofiltration spent caustic concentrate for refinery pH control applications can further reduce the operating expenditures. Overall, the pilot plant results obtained and the process economics evaluation data indicate a safer, environmentally friendly and highly competitive solution offered by the proposed nanofiltration treatment, thus representing a promising alternative to the use of conventional spent caustic treatment units. Highlights: Refinery wastewater UF treatment was found insufficient to meet discharge criteria. Refinery spent caustic NF treatment was successfully validated on a pilot scale. The 99.9% reduction in polar oil and grease content allows for caustic reuse. No NF permeate flux decrease was observed up to a volume concentration factor of 3. NF expected payback time of 1.1 years with savings of 1.5 M€/year were estimated.